Deixis of Persona, Space, and Time in the short stories Aku Bulan and Lautan Mimpi by Selly Fitriyani Wahyu - Dinda Ferika Khairunnisa; Dini Ananda Defi; Meilinda Tiara Putri; Rahmat Prayogi (Research in Education, Technology, and Multiculture, 2022)
Abstract: This article focuses on the deixis of charm, space and time contained in the short story Aku, Bulan dan Laut Mimpi by Selly Fitriyani Wahyu. Short stories can reveal various things conveyed by the author. Short stories have a meaning that can be studied from the field of literature. This article will present the diexistence of enchantment, space, and time using a qualitative descriptive research method. In this research, the writer found 130 data of charm deixis, 24 data of spatial deixis, and 12 data of time deixis.    Keywords: deixis, short story, Indonesian literature.